The Burning Truth(s) - R. Moore (South African Family Practice, 2014)
A severe burn is arguably the most significant injury that the human body can sustain. No other form of trauma causes the massive physiological changes seen in a patient with a major burn injury. This is true in the first few weeks as well as up to two years postburn, due to the persistence of the hypermetabolic response.1 Both the profound alterations in physiology as well as numerous anatomical changes make anaesthesia of the severely burned patient complex and challenging.